Ligand-specific activation of HER4/p180erbB4, a fourth member of the epidermal growth factor receptor family. - Plowman, G D (1993)
This report describes the isolation and recombinant expression of a cDNA clone encoding HER4, the fourth member of the human epidermal growth factor receptor (EGFR) family. The HER4/erbB4 gene encodes a 180-kDa transmembrane tyrosine kinase (HER4/p180erbB4) whose extracellular domain is most similar to the orphan receptor HER3/p160erbB3, whereas its cytoplasmic kinase domain exhibits 79% and 77% identity with EGFR and HER2/p185erbB2, respectively. HER4 is most predominantly expressed in several breast carcinoma cell lines, and in normal skeletal muscle, heart, pituitary, brain, and cerebellum. In addition, we describe the partial purification of a heparin-binding HER4-stimulatory factor from HepG2 cells. This protein was found to specifically stimulate the intrinsic tyrosine kinase activity of HER4/p180erbB4 while having no direct effect on the phosphorylation of EGFR, HER2, or HER3. Furthermore, this heparin-binding protein induces phenotypic differentiation, and tyrosine phosphorylation, of a human mammary tumor cell line that overexpresses both HER4 and HER2. These findings suggest that this ligand-receptor interaction may play a role in the growth and differentiation of some normal and transformed cells.